High-capacity and security molecular capsule transporters - Visessamit, Jakkapol; Kulsirirat, Kathawut; Yupapin, Preecha P. (My University, 2015)
Multiwavelength optical capsules can be generated and controlled by using soliton/Gaussian pulses within a nonlinear device system known as a “PANDA” ring circuit and system. The security of molecule/drug transportation can be formed by the strong coupling of soliton-like pulse, where the high-capacity optical capsules can be formed using the multiwavelength solitons, which can be a good advantage and combination of drug delivery to the required targets. Moreover, the multiple access of drug delivery can be formed using the optical networks, which allows the use of various drug molecules with variety of diagnosis and therapeutic applications.
Keywords: High-capacity transporter; High-security transporter; Molecular transporter; Optical capsule